Podeželski turizem v Spodnjem Podravju in regijska turistična ponudba - Korošec, Vladimir (Geografski vestnik, 2007)
Despite numerous and various tourist potentials Lower Podravje is not a completely developed or recognized tourist region which would be attracting more domestic and foreign guests. Regretfully we are slowly becoming aware of the necessity to shape and develop the recognized tourist region. The article deals with tourist service providers in the countryside of Lower Podravje and the links to the tourism of the whole region. The introduction describes the general features of the regional tourism development. The main part analyses in detail tourist service on holiday farms, deals with tourist - recreational paths, village events in the countryside and marketing.
Keywords: podeželje; rural area; tourism; turizem; turistična ponudba; kmečki turizem; Podravje